Olfactory behavior and response of household ants (Hymenoptera) to different types of coffee odor: A coffee-based bait development prospect - Abdul Hafiz, Ab Majid; Hamady, Dieng; Salbiah, Ellias; Faezah Syukriah, Sabtu; Abd Hafis, Abd Rahim; Satho, Tomomitsu (Elsevier B.V., 2018)
Odor sensation is a sensory modality of considerable significance in the foraging behavior and interactional organization of ants. In the food bait technology, smell is the basis of attraction, which, in turn, is the line of bait use and a key parameter for judging efficacy. Yet, the currently available baits possess low attractiveness to many ant pests. Hence, strategies to produce ant bait with increased attractiveness are needed. Despite evidence that coffee has a diverse aroma complex that affects the behavior of honey bees and ants, its attraction to house-invading ants has yet to be investigated. In a series of Y-tube olfactometer bioassays, we examined the behavioral responses of Tapinoma indicum (TI), Monomorium pharaonis (MP) and Solenopsis geminata (SG) to various coffee-induced odor stimuli, comprised of extracts from Arabica, Robusta and Liberica. All coffee extracts showed an influence on the behavior of TI, MP and SG workers, with Arabica showed the most significant influence to the tested ants. The workers of TI, MP and SG were more attracted to the odor of 0.01% Arabica extract (ONE), in comparison with 0.05% Arabica extract (TWO) or 0.10% Arabica extract (THREE). Arabica extract mixed with sugar (S) elicited a significant attraction from workers of all three species in a balanced competition with either unsweetened Arabica extract or water. These results indicated that coffee, particularly Arabica, was attractive to the foragers of TI, MP and SG, thus, the use of coffee as a novel stimulus agent seems plausible in ant bait development. © 2017